On the correlation between A-type scrambling and lack of Weak Crossover effects - Witkoś, Jacek (Adam Mickiewicz University, 2008)
This paper explores certain properties of word orders in Polish clauses with monotransitive verbs where the object is moved to the clause initial position across the subject. We briefly present two current accounts of such word orders in Russian (Baylin 2003 and Slioussar 2005, 2006) and conclude that both seem to capture certain properties of inverted constructions, though the genuine picture, at least for Polish, is still more complex. Most importantly, while OVS constructions unambiguously show that the movement of the object forms an A-type chain, OSV constructions are less straightforward, as the chain formed by the object can show both A-type and A-bar type properties. We propose a derivational account of this ambiguity and subsequently attempt to find a positive correlation between A-type properties of the fronting of the object and lack, or at least a strong suppression, of WCO effects in Polish.